MASYARAKAT ELITE DALAM AL-QUR’AN: (Sebuah Pendekatan Antropologi Al-Qur’an atas Term al-Mala’) - Muhamad Ali Mustofa Kamal (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2016)
Elite society in the series of the Qur’anic stories become interesting when those stories contain educational mission and enlightenment for mankind. The research uses descriptive-qualitative method with literary anthropological approach. The research focuses on how the implication of the attitude of elite society in the Qur'an. The research shows that the derivation of the word “al-mala'” ( ????? ) are mentioned 30 times in the Qur'an and spread in twelve surah, in the form of ma'rifat” (gnosis) for 29 times and in the form of “nakirah” for once only. Generally, the word “al-mala’” 'in the Qur'an refers to human, it is mentioned only two time that refers to angels namely in the Qur’an, chapter 37, verse 8 and chapter 38, verse 69. The type of “almala'” can be divided into three, namely propaganda against the apostle, who did not oppose the apostles preaching, and hypocrite. Term al-mala’ also has a relationship with kubara’) ????? ( and syaazah ) ???? ( describing the social construction of the society. Some valuable lessons and implications of the research results provide the urgency of the elite society behavior (al-mala') in the story of the Qur’an in the order of civilization. It shows the general trend of them, and the importance of elite cadres with the strengthening of theology and faith as they have a vital role in the progress and the collapse of a civilization.